2020
DOI: 10.1200/jco.20.01210
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Laparoscopic Distal Gastrectomy for Locally Advanced Gastric Cancer: The KLASS-02-RCT Randomized Clinical Trial

Abstract: PURPOSE It is unclear whether laparoscopic distal gastrectomy for locally advanced gastric cancer is oncologically equivalent to open distal gastrectomy. The noninferiority of laparoscopic subtotal gastrectomy with D2 lymphadenectomy for locally advanced gastric cancer compared with open surgery in terms of 3-year relapse-free survival rate was evaluated. PATIENTS AND METHODS A phase III, open-label, randomized controlled trial was conducted for patients with histologically proven locally advanced gastric aden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
200
0
7

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(214 citation statements)
references
References 24 publications
7
200
0
7
Order By: Relevance
“…Phase III clinical trials were conducted in Japan, South Korea, and China to examine the noninferiority of LDG to ODG for advanced gastric cancer. [34][35][36] The result of the primary analysis was first reported in the CLASS01 trial performed in China, which proved the noninferiority of LDG to ODG. Noninferiority was confirmed using the point estimation of 3-year relapse-free survival.…”
Section: Aparoscopi C Surg Erymentioning
confidence: 95%
See 1 more Smart Citation
“…Phase III clinical trials were conducted in Japan, South Korea, and China to examine the noninferiority of LDG to ODG for advanced gastric cancer. [34][35][36] The result of the primary analysis was first reported in the CLASS01 trial performed in China, which proved the noninferiority of LDG to ODG. Noninferiority was confirmed using the point estimation of 3-year relapse-free survival.…”
Section: Aparoscopi C Surg Erymentioning
confidence: 95%
“…On the other hand, LG for advanced gastric cancer has been considered to require further examination from the viewpoints of tumor handling, accuracy of D2 lymph node dissection, and safety. Phase III clinical trials were conducted in Japan, South Korea, and China to examine the noninferiority of LDG to ODG for advanced gastric cancer 34‐36 . The result of the primary analysis was first reported in the CLASS01 trial performed in China, which proved the noninferiority of LDG to ODG.…”
Section: Laparoscopic Surgerymentioning
confidence: 99%
“…SILS offers excellent cosmetic results because scarring is concealed in the umbilicus. There are a number of risks related to surgery, however, such as anastomotic leakage, delayed gastric emptying and intraabdominal abscesses [7,8]. There may also be short or long term decline in nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…There are RCTs from Korea demonstrating the oncologic equivalency of laparoscopic and open distal gastrectomy, although most focus on early gastric cancer and exclude patients undergoing total gastrectomy. 3 Due to the well-established differences in tumor biology and adverse prognostic factors between gastric adenocarcinoma from Eastern and Western countries, I will limit the discussion to the one Western RCT available. 4 In the Laparoscopic Versus Open Gastrectomy for Gastric Cancer (LOGICA) trial, investigators from ten experienced upper gastrointestinal centers in the Netherlands reported short-term outcomes of 227 patients.…”
mentioning
confidence: 99%